Resource recovery options in brewery effluent treatment using activated sludge and high rate algal ponds: assessing environmental impacts - Taylor, Richard Peter (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2020)
Wastewater treatment plants (WWTPs) are designed to clean effluents, but they also consume resources and produce waste. Various treatment technologies allow for the recovery of energy, nutrients and water from effluents turning this waste into products, which increases their sustainability and decreases the impact of WWTPs on the environment. There is a lack of literature which comprehensively compares the treatment performances, environmental impacts and beneficial downstream uses of the biomass generated by high rate algal pond (HRAP) and activated sludge (AS) treatment systems. This thesis aimed to compare (1) effluent treatment performance, (2) emissions and (3) downstream use of algae cultured in HRAP to sludge produced in AS and to obtain data to conduct a life cycle analysis (LCA) to compare the systems. The focus was on adding value to the effluent treatment process, while identifying the associated environmental impacts and contributing to the first ever zero-waste brewery effluent treatment system. Furthermore, these data were used to provide a basis to critically review and contribute to improving the methods used in the LCA of effluent treatment systems; particularly since this was the first wastewater treatment LCA that compared AS and HRAP using data collected from the same temporal and geographic location and from a single effluent stream. The electrical consumption water emission and land application of waste biomass caused the major environmental impacts of both treatment systems. The HRAP had less than 50 % of the electrical energy consumption (0.11±0.01 kW/m3 of effluent treated) compared to the AS system (0.29±0.11 kW/m3) which resulted in the technology having a lower climate change, photochemical oxidant formation, freshwater and marine ecotoxicity and fossil fuel depletion impact. It is imperative to understand the method of electrical energy (fossil fuel vs renewable) generation when conducting a LCA and deciding which technologies to use, since they have a major influence on the aforementioned impacts. The biogas yield of algal and sludge substrates was similar with an average gas production of 241 ml/g volatile solids fed. Biogas from algae fed digesters had a significantly higher methane content (64.73±0.81 %) and lower carbon dioxide content (22.94±0.24 %) when compared to WAS fed digesters (60.08±0.18 % and 27.37±0.43 %) respectively due to it being a less oxidised substrate. Swiss chard plants (Beta vulgaris) fertilised with anaerobically digested (AD) algae or sludge had a significantly higher mean biweekly yield (5.08±0.73 kg/m2) when compared to the inorganic-fertiliser control (3.45±0.89 kg/m2; p<0.0001). No difference was observed in the soil's physical fertility when algae or sludge were applied to the soil (p>0.05). The HRAP produced more biomass (317.18±27.76 g/m3) than the AS (83.12±64.91 g/m3), which resulted in a significantly greater downstream production of biogas and fertiliser per volume of effluent treated. According to the LCA, this also resulted in the HRAP system having a higher terrestrial ecotoxicity, due to the greater volume of solids and thus heavy metals applied to the soil. This interpretation can be misleading, because the mass of heavy metals released into the environment is the same for both systems, with a greater portion being applied to the land in the HRAP scenario and discharged into fresh water in the case of AS. Future LCA models should clarify if these biomasses are going to be applied to a single piece of land or multiple sites as this will influence the risk of contamination via pollutant build up in the soil. The application of sludge or algae on soil increased the soil's sodium concentration and sodium absorption ratio from 774.80±13.66 mg/kg to 952.17±34.89 mg/kg and 2.91±0.04 to 3.53±0.13, respectively. Regulations on the application of algae or sludge on agricultural soils should be altered to consider the limit values for sodium and future LCA's associated with effluent treatment facilities should incorporate the possibility of soil contamination through sodium build-up. This work also conceptualised the importance of reporting water emissions in wastewater treatment LCA in as much detail as possible, because this had a significant influence on the eutrophication impacts on water systems. Reporting water emissions as total nitrogen underestimated downstream eutrophication impacts compared with those using nitrogen-species concentration (ammonia, nitrite, nitrate etc). A marine eutrophication sensitivity co-efficient should be included in future LCA models which accounts for the probability of nitrogen and phosphorus emissions entering the coastal environment as well as the vulnerability of the marine environment to eutrophication. Activated sludge systems are favourable for situations where space is limited, were there are inadequate options for biomass disposal (biomass not be used in agriculture or AD) and were electricity is generated from a renewable source; whereas, HRAP are more suitable under circumstances where electricity production relies on fossil fuel that carries a high environmental impact and where options are available to use the biomass for economic gain such as biogas and fertiliser production. This thesis contributes towards a zero-waste brewery effluent treated process. The HRAP and AS treated effluent for reuse in the brewery or in agricultural irrigation. The solids were anaerobically digested, and the carbon was recovered as a biogas, while the digestate was applied as an agricultural fertiliser. This allowed for the recovery of water, nutrients and carbon.
Keywords: Sewage -- Purification -- Activated sludge process; Sewage disposal plants; Sewage -- Purification -- Biological treatament; Sewage -- Purification -- Nitrogen removal; Brewery waste; Breweries -- Waste disposal; Microalgae -- Biotechnology; Algal biofuels